Digital Infrastructure Management in the System of Socio-Cultural Institutions: the Archival Paradigm - Vasylenko, Daria; Butko, Larysa; Domitrak, Yuliya; Alistrenko, Nataliia (Socio-Cultural Management Journal, 2022)
Introduction. The management of the modern archival system should be characterized by the fundamental changes in all its areas, aimed at developing functions for the implementation of state policy in the field of digitalization, as well as developing principles of control in the archival information and search system, which will be implemented using digital technologies and will be able to guarantee the delivery of services to citizens. Purpose and methods. The method of the research is the clarification of promising vectors in the implementation of digital infrastructure in the management of archival institutions of Ukraine in the aspect of the implementation of the state policy of digitalization. To achieve this goal and to solve the research problems, the principles of objectivity and information theory and the traditional set of methods were used (method of systematic approach, structural method, method of situational research, methods of analysis and synthesis, methods of sociological, socio-psychological, pedagogical and managerial analysis, the method of survey). Results. The article analyzes the demand for innovative transformations in the archival sphere of Ukraine due to the development of digital technologies. A review of the supply of tools for the single archival information and search database as an element that unites the digitization potential of the archival system of Ukraine and put the system of archival management at the focus of collaboration with stakeholders. Conclusions. Using the new paradigm of archival management together with the implementation of digital infrastructure allows at the same time to improve the process of the archival management system and modernize the main mechanisms, taking into account current challenges.